Glucose uptake to guard cells via STP transporters provides carbon sources for stomatal opening and plant growth - Flütsch, Sabrina; Nigro, Arianna; Conci, Franco; Fajkus, Jiří; Thalmann, Matthias; Trtílek, Martin; Panzarová, Klára; Santelia, Diana (EMBO reports, 2020)
Guard cells on the leaf epidermis regulate stomatal opening for gas exchange between plants and the atmosphere, allowing a balance between photosynthesis and transpiration. Given that guard cells possess several characteristics of sink tissues, their metabolic activities should largely depend on mesophyll-derived sugars. Early biochemical studies revealed sugar uptake into guard cells. However, the transporters that are involved and their relative contribution to guard cell function are not yet known. Here, we identified the monosaccharide/proton symporters Sugar Transport Protein 1 and 4 (STP1 and STP4) as the major plasma membrane hexose sugar transporters in the guard cells of Arabidopsis thaliana. We show that their combined action is required for glucose import to guard cells, providing carbon sources for starch accumulation and light-induced stomatal opening that are essential for plant growth. These findings highlight mesophyll-derived glucose as an important metabolite connecting stomatal movements with photosynthesis.
Keywords: proteiny huseníčku; guard cells; uhlík; světlo; plant growth; stomatal opening; Plant Stomata; Glucose; Arabidopsis Proteins; Light; glukosa; průduchy rostlin; glucose; Arabidopsis; sugar transport protein; Carbon